Review of rare earth element (REE) adsorption on and desorption from clay minerals: Application to formation and mining of ion-adsorption REE deposits - Wu, Zhenxiao; Chen, Yu; Wang, Yang; Xu, Yuan; Lin, Zhuoling; Liang, Xiaoliang; Cheng, Hongfei (Ore geology reviews, 2023)
[Display omitted] •The metallogenic mechanism of ion-adsorption REE deposits is reviewed.•The mineral evolution of clay minerals during deposit formation is discussed.•The REE adsorption mechanism by clay minerals is summarised.•The controlling factors of REE leaching from clay minerals are determined. Ion-adsorption rare earth elements (iREE) deposits are the globally predominant source of heavy rare earth elements (HREE), which are mainly discovered and mined in southern China. This paper reviews the genesis and mining mechanisms of iREE deposits. These deposits are mainly formed in the weathering crust of rare earth elements (REE)-rich granites, volcanic rocks and metamorphic rocks. During the weathering and eluviation, REE are released by the dissolution of REE-bearing minerals, depending on the weathering resistance of such minerals. Then, aqueous REE cations migrate downwards and are adsorbed by clay minerals. The adsorption and fractionation of REE are affected by variations in oxygen, pH and ionic species and strength. REE are mainly adsorbed on clay minerals through ion exchange and surface complexation. The former reaction cannot cause evident REE fractionation, whereas the latter induces an enrichment of HREE over LREE. The enrichment and fractionation characteristics of REE are also constrained by their occurrence states. REE with different occurrence states can be distinguished via sequential extraction, and the micro-occurrence states of REE can be probed using high-sensitivity, high-resolution characterisation. Furthermore, the leaching mechanism of iREE deposits is summarized, where REE are exchanged by foreign cations. Ammonium sulphate is the main leaching agent, but its excessive use can cause serious environmental pollution. Thus, leaching agents with little or no ammonium, such as MgSO4 and CaCl2, have been recommended. The controlling factors of REE leaching are the concentration of leaching agents, pH, temperature and solid/liquid ratio. The above summary deepens the understanding of the formation mechanism of iREE deposits and provides beneficial information for the efficient but green mining of iREE deposits.